Analysis of the need for financial education in collegiate formation - Céspedes López, Jairo Beymar (2018)
Financial education is an important factor in the life of any person, consumption, savings, investment and other basic concepts of finance are unknown by much of the population in the world, this article identifies certain attitudes against it and proposes, in a basic way, fundamental pillars of financial education that could be implemented in secondary education, considering that it should be implemented as a curricular subject in education.